2017
DOI: 10.1371/journal.pone.0172849
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of a novel method for the screening of deep vein thrombosis by using a combined D-dimer- and age-based index before total hip arthroplasty

Abstract: Plasma D-dimer level is clinically useful for diagnosing patients with suspected deep vein thrombosis (DVT). However, the cut-off value for the D-dimer level remains controversial and undetermined with regard to total hip arthroplasty (THA). The objective of this study was to estimate the efficacy of an age- and D-dimer-based index for diagnosing DVTs in asymptomatic cases before THA. We enrolled 224 patients with no symptoms associated with DVT before THA. All the patients underwent ultrasonography, and the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
18
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 19 publications
6
18
2
1
Order By: Relevance
“…Although previous literature has established the incidence and risk factors of DVT after primary THA, a lack of consensus has been conducted [ 16 ]. Our results have indicated an incidence of 9.5% for DVT after unilateral primary THA, which was relatively higher than previous reports [ 3 , 17 ]. We considered that the different races, ages, and inclusion criteria might lead to the different results.…”
Section: Discussioncontrasting
confidence: 72%
“…Although previous literature has established the incidence and risk factors of DVT after primary THA, a lack of consensus has been conducted [ 16 ]. Our results have indicated an incidence of 9.5% for DVT after unilateral primary THA, which was relatively higher than previous reports [ 3 , 17 ]. We considered that the different races, ages, and inclusion criteria might lead to the different results.…”
Section: Discussioncontrasting
confidence: 72%
“…In previous reports, Norio Imai et al demonstrated that age and D-dimer index can be useful in screening patients for DVTs before THA. [13] The conclusion was similar to us. Moreover, age-adjusted D-dimer value was calculated as patients' age times 0.01(µg/mL) by Henrike J Schouten et al [10] They drew conclusions that age-adjusted D-dimer value can increase speci city, whereas sensitivity was not.…”
Section: Discussionsupporting
confidence: 84%
“…Deep venous thrombosis (DVT) is a common complication of SCI, with clinical features of lower-limb swelling and edema. Serum D-dimer is a breakdown product of fibrin, which serves as a useful diagnostic marker for DVT [ 19 22 ]. It has been reported that the incidence rate of DVT was 6.55% in acute SCI patients, and the incidence rate of NHO was 8%, with a correlation between the DVT and NHO [ 23 ].…”
Section: Discussionmentioning
confidence: 99%